If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -3)(x + 4) = (x + 4) + -1 Reorder the terms: (-3 + x)(x + 4) = (x + 4) + -1 Reorder the terms: (-3 + x)(4 + x) = (x + 4) + -1 Multiply (-3 + x) * (4 + x) (-3(4 + x) + x(4 + x)) = (x + 4) + -1 ((4 * -3 + x * -3) + x(4 + x)) = (x + 4) + -1 ((-12 + -3x) + x(4 + x)) = (x + 4) + -1 (-12 + -3x + (4 * x + x * x)) = (x + 4) + -1 (-12 + -3x + (4x + x2)) = (x + 4) + -1 Combine like terms: -3x + 4x = 1x (-12 + 1x + x2) = (x + 4) + -1 Reorder the terms: -12 + 1x + x2 = (4 + x) + -1 Remove parenthesis around (4 + x) -12 + 1x + x2 = 4 + x + -1 Reorder the terms: -12 + 1x + x2 = 4 + -1 + x Combine like terms: 4 + -1 = 3 -12 + 1x + x2 = 3 + x Solving -12 + 1x + x2 = 3 + x Solving for variable 'x'. Reorder the terms: -12 + -3 + 1x + -1x + x2 = 3 + x + -3 + -1x Combine like terms: -12 + -3 = -15 -15 + 1x + -1x + x2 = 3 + x + -3 + -1x Combine like terms: 1x + -1x = 0 -15 + 0 + x2 = 3 + x + -3 + -1x -15 + x2 = 3 + x + -3 + -1x Reorder the terms: -15 + x2 = 3 + -3 + x + -1x Combine like terms: 3 + -3 = 0 -15 + x2 = 0 + x + -1x -15 + x2 = x + -1x Combine like terms: x + -1x = 0 -15 + x2 = 0 The solution to this equation could not be determined.
| 5-3a=28 | | 25x^2-11x+210=0 | | 5+3(2x-1)=2(3x+1)-1 | | 100=5/2(b+12) | | 7-3y=27+2y | | y-1.5=2 | | (27x^3)^(1/3) | | 0.5m=6 | | f(x)=X^3-9X^2+15x+5 | | 4(2x)+55=2820 | | x*6=6.3 | | 89+5x-7+x=x+14x+1 | | cosx=5x | | x^2/x=10 | | 2x^3-12x^2+16x+0=0 | | 89+5x-7+x=x+14+1 | | x÷1/2=-3/4 | | 6n^2+45n+75=0 | | 38=8x-10 | | 2x(-3)-4x=15-(X+6) | | 5x-12x=-40-16 | | 4x-2x+5=55 | | y^2=cos(2x) | | (X+1)(x+4)=24 | | n/-4=-9-(-7) | | x-.005x=x-40 | | 7*x+2=2*x+37 | | Z^2+12z=0 | | f(x)=2x^3-12x^2+16x | | x-.5x=x-40 | | (x^4-y^4)/(25a^4-16b^4) | | 4x+5*3x-3= |